The improving electrochromic performance of nickel oxide film using aqueous N,N-dimethylaminoethanol solution - Park, Sun Ha; Lim, Ju Wan; Yoo, Sung Jong; Cha, In Young; Sung, Yung-Eun (ELSEVIER, 2012)
New nickel oxide thin films with a micro-scale thickness and porous structure were fabricated using a sol-gel method in a mixed solvent containing N,N-dimethylaminoethanol (dmaeH) and distilled water at a 1:1 ratio. After annealing, the deposited film transformed to a well oriented, porous nickel oxide thin film. This nickel oxide thin film showed enhanced charge capacity and greater optical transmittance changes in a lithium-based electrolyte, and may be applied to WO3/Li+-based electrolyte/NiO electrochromic devices requiring long cycles. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: DEVICES; WO3